TEACHER'S EFFORTS IN IMPROVING AL-QUR'AN READING ABILITY FOR STUDENTS OF CLASS V AT MI NURUL HARAMAIN NARMADA - Ridwan; Noer Sari Fanny (Universitas Islam Negeri Mataram, 2023)
The ability to read the Koran can be interpreted as the child's ability to be able to pronounce or recite what is written in the holy book of the Koran correctly according to makhraj and the rules of tajwid science. This study aims to, (1) analyze the teacher's efforts in improving the ability to read the Qur'an for fifth grade students at NW Nurul Haramain Narmada Elementary School, 2) describe the obstacles in improving the ability to read the Koran for fifth grade students at Nurul Haramain Narmada. This study used a qualitative approach, data collection techniques using observation, interviews and documentation. Data were analyzed using a qualitative research flow starting from data reduction techniques, data presentation, and drawing conclusions/data verification. Sources of data for this research were obtained from school principals, religious teachers who teach the Koran and fifth grade students of Islamic elementary schools. The results of this study indicate that 1) Efforts made by the teacher in improving the ability to read the Qur'an by forming groups (Khalaqoh model) based on ability level, then carrying out intensive coaching and continuously monitoring the progress of adopting the khalaqoh qiroati model using level, for students who have been assessed as capable according to the standards set by the school, then they can continue with learning the science of recitation, then students who are in grade 3 are placed in dormitories to monitor the development of their abilities by the teacher, and read murottal.